Compulsory community service for dentists - Opportunity for meaningful reform - Machete, Motimedi L; Makwakwa, Nokukhanya L; Moipolai, Pusetso D; Motloba, Pagollang D (South African Dental Journal, 2021)
Previous studies indicate that the delivery of the compulsory community service (CS) programme was far from the intended objectives. It is plausible that the intended vision of the programme for the young graduates to“…develop skills, acquire knowledge, behaviour patterns and critical thinking that would help in their professional development and future careers.” may not be realizable. This study evaluated the extent to which CS programme nenabled CS dentists to develop clinical skills. A national cross-sectional study was undertaken on CS dentists. Adapted visual analogue scale (VAS) assessed the frequency of work performed and levels of skills or competency acquired. A total of 217/235 dentists participated, (response rate of 92.34%). The clinical work undertaken and skills/competence acquired were positively correlated; [Mean (SD)= 1.10 (0.326), 1.10 (0.359); r =0.945, p=<0.000, n = 217] respectively. This finding validates the associated loss of skills and competence because of lack of clinical exposure during CS. Specialised dental procedures were never or rarely performed during CS (89.5%). Similarly the level of skills acquired during CS was minimal. CS in its present form disrupts continuing education and the development of learning and clinical skills. These cohorts of dentists have entered independent practice less prepared; may fail to provide quality care to the public. The CS programme is regressive, and requires urgent review and reform.